2022
DOI: 10.1111/tbed.14581
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomic profiling reveals diverse tick‐borne bacteria, protozoans and viruses in ticks and wildlife from Australia

Abstract: Tick-borne zoonoses are emerging globally due to changes in climate and land use.While the zoonotic threats associated with ticks are well studied elsewhere, in Australia, the diversity of potentially zoonotic agents carried by ticks and their significance to human and animal health is not sufficiently understood. To this end, we used untargeted metatranscriptomics to audit the prokaryotic, eukaryotic and viral biomes of questing ticks and wildlife blood samples from two urban and rural sites in New South Wale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 130 publications
1
14
0
Order By: Relevance
“…Possible transovarial transmission was reported once for T. rhipicephalis in artificially infected R. sanguineus [25], but we did not observe evidence of maternal transmission in I. ricinus, suggesting that this transmission route may be a biological trait variable between members of the T. pestanai clade. Transstadial transmission for members of the T. pestanai clade is probable at least in I. ricinus and A. oblongoguttatum since we detected infections in unfed ticks (meaning that they have digested their previous blood meals and have further moulted), a pattern also previously observed in I. ricinus, I. holocyclus, A. triguttatum and Haemaphysalis bancrofti [12,14,24].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Possible transovarial transmission was reported once for T. rhipicephalis in artificially infected R. sanguineus [25], but we did not observe evidence of maternal transmission in I. ricinus, suggesting that this transmission route may be a biological trait variable between members of the T. pestanai clade. Transstadial transmission for members of the T. pestanai clade is probable at least in I. ricinus and A. oblongoguttatum since we detected infections in unfed ticks (meaning that they have digested their previous blood meals and have further moulted), a pattern also previously observed in I. ricinus, I. holocyclus, A. triguttatum and Haemaphysalis bancrofti [12,14,24].…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, while I. ricinus is the tick species most commonly biting humans in Western Europe [41], in the present study, we found that 4% of field specimens were infected with a trypanosome of the T. pestanai clade. In Australia, a significant human-biting tick, I. holocyclus, was frequently found infected by T. giletti [24]. Humans are therefore exposed to bites of Trypanosoma-infected ticks without the risk of infection being documented to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newport Tick virus (also named Ixodes holocyclus jingmenvirus) was identified in a metagenomics study of ticks from New South Wales in Australia ( Gofton et al, 2022 ). The sequences were detected in relatively high prevalence in I. holocylcus ticks from Kioloa and Sydney.…”
Section: Tick- and Vertebrate-associated Jingmenvirusesmentioning
confidence: 99%
“…The answer may be that the native tick fauna are unique due to the continent's long geological isolation since the Gondwanan break-up some 130-135 million years ago [25,26]. Indeed, recent metagenomic and metatranscriptomic analyses have revealed a diverse microbiota in Australian ticks comprising known bacterial, viral, and protozoal genera and novel species that are related to, yet phylogenetically distinct from, northern hemisphere tick-borne pathogens [19,[27][28][29][30][31][32][33][34][35]. In other words, separate evolutionary and ecological pathways have resulted in not only a unique mammalian fauna but may also have impacted tick-associated microbial communities on the Australian continent.…”
Section: Introductionmentioning
confidence: 99%